Empowering American Indian and Alaska Native youth to lead measurement development of an indigenous adolescent wellbeing measure: A protocol paper - Quintana, Sierra; Ivanich, Jerreed D.; Pikok, Kimberly; Nez, Shanoa; Zepeda, Zenetta (Frontiers in Public Health, 2022)
Background American Indian and Alaska Native youth research has rarely included young people from within these populations as codesigners. In addition to the lack of youth involvement, most findings focus on presenting statistics around disparity versus focusing on this population's unique strengths and resiliency. The research design of this protocol aims to fill this gap in the current literature. Methods To address this discrepancy, a multipronged approach to youth and young adult participatory research was implemented. These prongs include a virtual gathering where the Nominal Group Technique was conducted, an assembly of a youth Research Design Team. Lastly, the research team will implement a protocol developed by the Research Design Team. The Research Design Team plans to conduct qualitative interviews and distribute a web-based quantitative survey with a raffle as respondent compensation. This protocol is a preliminary phase to developing a wellbeing measure for AIAN youth. Discussion Having an operationalized definition of wellness from AIAN youth will fill a gap in the current body of research with optimism that this will lead to additional studies exploring the AIAN youth voice.